2021
DOI: 10.1021/acsomega.1c00263
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hg2+ by a Dual-Fluorescence Ratio Probe Constructed with Rare-Earth-Element-Doped Cadmium Telluride Quantum Dots and Fluorescent Carbon Dots

Abstract: Quantum dots (QDs) and carbon quantum dots (CDs) are classes of zero-dimensional materials whose sizes can be ≤10 nm. They exhibit excellent optical properties and are widely used to prepare fluorescent probes for qualitative and quantitative detection of test objects. In this article, we used cerium chloride as the cerium source and used the in situ doped cerium (rare-earth element) to develop cadmium telluride (CdTe) quantum dots following the aqueous phase method. CdTe: Ce quantum dots were successfully syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…3D. TC can cooperate with Eu 3+ and act as the "antenna" to transmit the absorbed energy to Eu 3+ , 6 which can be proved by UV absorption spectra. Compared with that without TC, the absorption peaks of CDs-Eu and TC display an obvious red shift, while the emission peaks corresponding to Eu 3+ are enhanced (Fig.…”
Section: Sensing Mechanismmentioning
confidence: 98%
See 1 more Smart Citation
“…3D. TC can cooperate with Eu 3+ and act as the "antenna" to transmit the absorbed energy to Eu 3+ , 6 which can be proved by UV absorption spectra. Compared with that without TC, the absorption peaks of CDs-Eu and TC display an obvious red shift, while the emission peaks corresponding to Eu 3+ are enhanced (Fig.…”
Section: Sensing Mechanismmentioning
confidence: 98%
“…Based on these advantages, lanthanidebased nanomaterials have received increasing attention. 6,7 The combination of CDs with lanthanide metal complexes is expected to achieve double-emission ratiometric fluorescence with high sensitivity. There are currently two approaches to functionalize CDs, namely elemental doping and surface modification.…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium quantum dots can also be used in conjugation with any rare earth metals of choice (Chu, H 2021) and ii) Pesticides with -Cl groups tend to have a higher binding affinity with the quantum dot which in turn may lead to higher chance of degradation of the pesticide (Sahoo, D 2018). Two recent reports suggested that functionalization of PbS quantum dots with gelatin has successfully lead to the detection of notorious pesticides like bentazon at a range of 0.05-200 ng/mL (Marahel, F 2022).…”
Section: Carbon Quantum Dotsmentioning
confidence: 99%
“…40 In recent years, many researchers have blended CdTe and CQDs solutions to prepare a dual fluorescence detection system. 41,42…”
Section: Introductionmentioning
confidence: 99%